2020
DOI: 10.1002/cctc.202001537
|View full text |Cite
|
Sign up to set email alerts
|

Triphenylphosphine as Efficient Antidote for the Sulfur‐Poisoning of the Pd/C Hydrogenation Catalyst

Abstract: Pd/C catalyst is a widely applied hydrogenation catalyst in organic synthesis for the reduction of many organic compounds. It has been reported that it suffers from sulfur poisoning. Herein we report that catalytic amounts of triphenylphosphine (TPP), which is also an usual poison to Pd/C, could greatly improve the catalytic performance of Pd/C in sulfur‐containing systems. The sulfur‐poisoned Pd/C catalyst can be activated when adding TPP. The characterizations show that TPP partly reduced the deactivated lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…6−8 Zhang and co-workers reported that the triphenylphosphine ligand could significantly improve the activity of Pd/C in the sulfur-containing reaction system by slowing down the sulfidation on Pd to regenerate the active metallic Pd surface in the hydrogenation of 4-nitroanisole at high temperature. 9 Pt/SOD-H and Pt/SOD-M (M = Mg, Ca, and Ba) have been reported to show high sulfur-poisoning resistance properties due to the shape selectivity and hydrogen spillover in benzene hydrogenation in the presence of sulfur compounds, e.g., H 2 S and thiophene. 10 The alloying of Cr or W with Pd increases the antisulfur ability of Pd in toluene hydrogenation in the presence of thiophene, possibly due to the increased surface electron deficiency of Pd.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6−8 Zhang and co-workers reported that the triphenylphosphine ligand could significantly improve the activity of Pd/C in the sulfur-containing reaction system by slowing down the sulfidation on Pd to regenerate the active metallic Pd surface in the hydrogenation of 4-nitroanisole at high temperature. 9 Pt/SOD-H and Pt/SOD-M (M = Mg, Ca, and Ba) have been reported to show high sulfur-poisoning resistance properties due to the shape selectivity and hydrogen spillover in benzene hydrogenation in the presence of sulfur compounds, e.g., H 2 S and thiophene. 10 The alloying of Cr or W with Pd increases the antisulfur ability of Pd in toluene hydrogenation in the presence of thiophene, possibly due to the increased surface electron deficiency of Pd.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies have been reported to enhance the antisulfur poisoning properties of supported metal catalysts. Zhang and co-workers reported that the triphenylphosphine ligand could significantly improve the activity of Pd/C in the sulfur-containing reaction system by slowing down the sulfidation on Pd to regenerate the active metallic Pd surface in the hydrogenation of 4-nitroanisole at high temperature . Pt/SOD-H and Pt/SOD-M (M = Mg, Ca, and Ba) have been reported to show high sulfur-poisoning resistance properties due to the shape selectivity and hydrogen spillover in benzene hydrogenation in the presence of sulfur compounds, e.g., H 2 S and thiophene .…”
Section: Introductionmentioning
confidence: 99%
“…One of the known methods to prevent the poisoning of Pd/C by monomers is using triphenylphosphine (TPP) as an antidote for S poisoning. 40 It is known that the sulfidation of Pd on the surface slows down and prevents the aggregation of active centers during the reaction on adding TPP. C. Amatore et al presented a new reduction pathway of Pd( ii ) to Pd(0) induced by TPP, and later, C. Amatore and A. Jutand suggested a mechanism of Pd-catalyzed cross-coupling that contains favorable anionic palladium intermediates with TPP.…”
Section: Resultsmentioning
confidence: 99%
“…Since two protecting groups were needed, the orthogonal groups Cbz and Boc were considered. Because the sulfur‐containing dithiocarbazate function could interfere with the hydrogenolytic cleavage of the Cbz‐protecting group by catalyst poisoning, [ 37 ] the positioning was chosen accordingly. The required building block 20 for this strategy was obtainable by N ‐amination of Boc‐piperazine with reagent 19 .…”
Section: Resultsmentioning
confidence: 99%
“…R poisoning, [37] the positioning was chosen accordingly. The required building block 20 for this strategy was obtainable by N-amination of Boc-piperazine with reagent 19.…”
Section: Compoundmentioning
confidence: 99%